Transglutaminase 2 regulates endothelial cell calcification via IL-6-mediated autophagy - Liu, Bo; Cai, Zhiyuan; Wang, Yan; Liu, Xinye; Zhang, Bin; Zheng, Qian; Li, Jingye; Li, Cien; Cui, Yuanbo; Lv, Pengju; Yang, Dongwei (Frontiers in Pharmacology, 2024)
Introduction Endothelial cell (EC) calcification is an important marker of atherosclerotic calcification. ECs play a critical role not only in atherogenesis but also in intimal calcification, as they have been postulated to serve as a source of osteoprogenitor cells that initiate this process. While the role of transglutaminase 2 (TG2) in cellular differentiation, survival, apoptosis, autophagy, and cell adhesion is well established, the mechanism underlying the TG2-mediated regulation of EC calcification is yet to be fully elucidated. Methods The TG2 gene was overexpressed or silenced by using siRNA and recombinant adenovirus. RT-PCR and WB were used to analyze the relative expression of target genes and proteins. 5-BP method analyzed TG2 activity. mCherry-eGFP-LC3 adenovirus and transmission electron microscopy analyzed EC autophagy level. Calcium concentrations were measured by using a calcium colorimetric assay kit. Alizarin red S staining assay analyzed EC calcification level. Elisa analyzed IL-6 level. Establishing EC calcification model by using a calcification medium (CM). Results Our findings demonstrated that CM increased TG2 activity and expression, which activated the NF-κB signaling pathway, and induced IL-6 autocrine signaling in ECs. Furthermore, IL-6 activated the JAK2/STAT3 signaling pathway to suppress cell autophagy and promoted ECs calcification. Discussion ECs are not only critical for atherogenesis but also believed to be a source of osteoprogenitor cells that initiate intimal calcification. Previous research has shown that TG2 plays an important role in the development of VC, but the mechanism by which it exerts this effect is not yet fully understood. Our results demonstrated that TG2 forms complexes with NF-κB components inhibition of autophagy promoted endothelial cell calcification through EndMT. Therefore, our research investigated the molecular mechanism of EC calcification, which can provide new insights into the pathogenesis of atherosclerosis.